Combining Minimally Invasive Techniques in Managing a Frail Patient with Postpneumonectomy Bronchopleural Fistula. (7th April 2021) - Kostopanagiotou, Kostas; Filippiadis, Dimitrios; Bakas, Efthimios; Thomas, Costas; Kostroglou, Andreas; Elias, Santaitidis; Sidiropoulou, Tatiana; Tsiodras, Sotirios; Tomos, Periklis
Abstract : A postpneumonectomy bronchopleural fistula is a life-threatening complication requiring aggressive treatment and early repair. Reoperations are common due to initial treatment failure. Advanced bronchoscopic techniques are rapidly evolving, but permanent results are questionable. We report the minimally invasive management of a frail 79-year-old patient with postpneumonectomy fistula in respiratory failure due to repeated infections. Previous bronchoscopic closure attempts with fibrin failed. The multistep interdisciplinary management included airway surveillance by virtual bronchoscopy, percutaneous fibrin glue instillation under computed tomography, and awake thoracoscopic surgery to achieve temporary closure. This provided an acceptable long period of symptomatic and physical improvement. The bronchial stump failed again four months later, and the patient succumbed to pneumonia. Pneumonectomy has to be avoided unless strongly indicated. Complications are best managed with surgery for definite treatment. We emphasize our approach only when a patient declines surgery or is medically unfit as a temporary time-buying strategy in view of definite surgery in a high-volume center.